1995
DOI: 10.1051/animres:19950406
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of vitamin C in plasma and milk of dairy cattle

Abstract: Summary — Colostrum or milk samples from 6 cows and blood plasma samples from the cows and their calves were taken between 0 and 28 d after calving and analyzed for vitamin C (ascorbic acid). At birth, the blood plasma concentration of ascorbic acid in calves ranged between 6.1 and 10.8 pg/ml, and declined within 5 d to between 2.7 and 4.5 wg/ml. Correspondingly, the concentration was twice as high in colostrum (16 pg/ml) than in milk at 2 d after calving (8 pg/ml). The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
2
8
1
Order By: Relevance
“…It would appear that newborn camel and dairy calves depend on colostrum as a source of vitamin C. There is evidence that vitamin C stimulates the immune response in calves (Cummins and Brunner, 1989). In keeping with Witnah and Riddell (1977), Hidiroglou and colleagues (1995) also reported relatively low ascorbic acid concentrations for cow milk. From a metabolic point of view, it is interesting to study the basis for the species difference in ascorbic acid concentration and cow milk.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It would appear that newborn camel and dairy calves depend on colostrum as a source of vitamin C. There is evidence that vitamin C stimulates the immune response in calves (Cummins and Brunner, 1989). In keeping with Witnah and Riddell (1977), Hidiroglou and colleagues (1995) also reported relatively low ascorbic acid concentrations for cow milk. From a metabolic point of view, it is interesting to study the basis for the species difference in ascorbic acid concentration and cow milk.…”
Section: Discussionsupporting
confidence: 86%
“…Ascorbic acid concentrations were found to be on average 10% higher in colostrum than in milk obtained at 4–5 months after parturition. Hidiroglou and colleagues (1995) obtained a level of 16 mg/l in colostrum and 8 mg/l in milk of Canadian Holstein cows. It would appear that newborn camel and dairy calves depend on colostrum as a source of vitamin C. There is evidence that vitamin C stimulates the immune response in calves (Cummins and Brunner, 1989).…”
Section: Discussionmentioning
confidence: 94%
“…There is a limited absorption of ascorbic acid at high dose levels and levels of ascorbic acid in the tissues cannot be increased appreciably by ingesting large doses of vitamin C (Rivers, 1987). Supplementation of crystalline Lascorbic acid and L-ascorbyl-2-polyphosphate in broiler chicken diet and drinking water found no consistent differences in plasma ascorbic acid concentrations, relative to vitamin source (Pardue et al, 1993 (Richetti, 1987), but was similar to the one reported for calves just after birth (Hidiroglou et al, 1995 …”
supporting
confidence: 75%
“…Vitamin C concentration in cows' milk also depends on the stage of lactation, but changes in its concentration differ from that in the analysed mares' milk. Hidiroglou et al observed that the concentration of vitamin C in cows' milk decreased with the progress of lactation. Human milk is a richer source of vitamin C than cows' milk and its content also changes with the stage of lactation and is greater in colostrum than in milk …”
Section: Resultsmentioning
confidence: 99%